(untitled) (Bioagro, 2022)
Cañihua is a very important crop in the diet of the Peruvian and Bolivian Andean highlands’ population due to the high protein quality of its grains. The Germplasm Bank of Andean Crops of Universidad Nacional del Altiplano, located in Puno, Peru, has around 400 accessions of this species, many of which do not have a standardized description that could serve as a basis for research aiming crop production improvement. The objective of this work was to characterize morphologically and agronomically 27 accessions of cañihua compared with 3 commercial varieties. The evaluated traits were plant height, number of branches, vegetative cover, length, width and number of teeth of the leaf blade, diameter and test weight of the grain, yield and harvest index, along with the number of days to branching, flowering, milky and pasty grain, and physiological maturity. The results indicate that among the varieties, the highest yield was shown by INIA-406, while Cupi and Ramis were the earliest ones. Cupi has higher yield than Ramis, although its grains are smaller. The accessions showed high variability among them and the accession 03-21-23 stood out for its high yield and the 03-21-315 for having the largest grain size, although low yield. Accession 03-21-7 showed the highest plant height and 03-21-246 the largest canopy, both with acceptable yields. It is concluded on the convenience of undertaking the improvement of the genetic stability of these four accessions